International Journal of Algebra and Statistics Volume 6: 1-2(2017), 56-80 DOI :10.20454/ijas.2017.1266
Published by Modern Science Publishers Available at: http://www.m-sciences.com
Representation of Graph Structure Based on I-V Neutrosophic Sets Muhammad Akram and Muzzamal Sitara Department of Mathematics, University of the Punjab, New Campus, Lahore, Pakistan (Received: 10 Febrary 2017; Accepted: 15 April 2017)
Abstract. In this research article, we apply the concept of interval-valued neutrosophic sets to graph structures. We present the concept of interval-valued neutrosophic graph structures. We describe certain operations on interval-valued neutrosophic graph structures and elaborate them with appropriate examples. Further, we investigate some relevant properties of these operators. Moreover, we propose some open problems on interval-valued neutrosophic line graph structures.
1. Introduction Zadeh [26] proposed fuzzy set theory to deal with uncertainty in many meticulous real-life phenomenons. Fuzzy set theory is affluently applicable in real time systems having information with different levels of precision. Zadeh introduced interval-valued fuzzy sets as generalization of fuzzy sets in [27]. There are many natural phenomenons, in which with membership value it is necessary to consider non-membership value. Membership value of an event is in its favor, whereas non-membership value is in its opposition. Atanassov [10] introduced the notion of intuitionistic fuzzy sets as an extension of fuzzy sets. Intuitionistic fuzzy sets are more practical, advantageous and applicable in many real-life phenomenons. In many reallife phenomenons like information fusion, indeterminacy is doubtlessly quantified. Smarandache [19, 20] proposed the notion of neutrosophic sets, he combined non-standard analysis, tricomponent logic, and philosophy. “It is a branch of philosophy which studies the origin, nature and scope of neutralities as well as their interactions with different ideational spectra”. In neutrosophic set, three independent components are: truth-membership (t), indeterminacy-membership (i) and falsity-membership ( f ), each membership value is a real standard or non-standard subset of the non-standard unit interval ]0− , 1+ [ and there is no restriction on their sum. For convenient and advantageous use of neutrosophic sets in science and engineering, Wang et al. [22] introduced the idea of single-valued neutrosophic(SVN) sets, whose three independent components t, i and f have values in standard unit interval [0, 1] and their sum does not exceed three. Neutrosophic set theory is a generalization of the fuzzy set theory and intuitionistic fuzzy set theory. It is more advantageous and applicable in many fields, including medical diagnosis, control theory, topology, decision making problems and in many more real-life problems. Wang et al. [23] presented the notion of interval-valued neutrosophic sets, it is more precise and more flexible as compared to single-valued neutrosophic set. An interval-valued neutrosophic set is a generalization of the concept of single-valued neutrosophic set, in which values of three independent components (t, i, f ) are intervals, which are subsets 2010 Mathematics Subject Classification. 03E72, 05C72, 05C78, 05C99. Keywords. Graph structure, interval-valued neutrosophic graph structure. Email address: m.akram@pucit.edu.pk, muzzamalsitara@gmail.com (Muhammad Akram and Muzzamal Sitara)
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
57
of standard unit interval [0, 1]. On the basis of Zadeh’s fuzzy relations [28], Kaufmann proposed fuzzy graph [15]. Rosenfeld [17] discussed fuzzy analogue of various graph-theoretic ideas. Later on, Bhattacharya [11] gave some remarks on fuzzy graphs, and some operations on fuzzy graphs were introduced by Mordeson and Peng [16]. The complement of a fuzzy graph was defined by Mordeson [16] and further studied by Sunitha and Vijayakumar [21]. Hongmei and Lianhua gave the definition of interval-valued fuzzy graph in [14]. After that, Akram et al. [1–4] considered several concepts on interval-valued fuzzy graphs. Recently, Akram and Nasir [5] dealt with interval-valued neutrosophic graphs. Akram and Shahzadi [6] introduced the notion of neutrosophic soft graphs with applications. Akram [7] introduced the notion of single-valued neutrosophic planar graphs. Dinesh and Ramakrishnan [13] defined fuzzy graph structures and discussed its properties. Akram and Akmal [9] proposed the notion of bipolar fuzzy graph structures. In this research article, we first present the concept of interval-valued neutrosophic line graphs as an extension of interval-valued fuzzy line graphs [1]. We then present concept of interval-valued neutrosophic graph structures. Further, we describe certain operations on interval-valued neutrosophic graph structures. Finally, we state some open problems on interval-valued neutrosophic line graph structures. 2. Background Wang et al. [23] introduced the concept of interval-valued (I-V) neutrosophic sets as follows: Definition 2.1. [23, 24] The interval-valued neutrosophic set A in X is defined by A = {(x, [t−A(x), t+A(x)], [i−A(x), i+A(x)], [ fA− (x), fA+ (x)]) : x ∈ X}, where, t−A (x), t+A (x), i−A (x), i+A (x), fA− (x), and fA+ (x) are neutrosophic subsets of X such that t−A (x) ≤ t+A (x), i−A (x) ≤ i+A (x) and fA− (x) ≤ fA+ (x) for all x ∈ X. For any two interval-valued neutrosophic sets A = ([t−A (x), t+A(x)], [i−A(x), i+A(x)], [ fA− (x), fA+ (x)]) and B = ([t−B (x), t+B (x)], [i−B (x), i+B (x)], [ fB− (x), fB+ (x)]) in X, we define: • A ∪ B = {(x, max(t−A (x), t−B (x)), max(t+A (x), t+B (x)), max(i−A (x), i−B (x)), max(i+A (x), i+B (x)), min( fA− (x), fB− (x)), min( fA+ (x), fB+ (x))) : x ∈ X}. • A ∩ B = {(x, min(t−A (x), t−B (x)), min(t+A (x), t+B (x)), min(i−A (x), i−B (x)), min(i+A (x), i+B (x)), max( fA− (x), fB− (x)), max( fA+ (x), fB+ (x))) : x ∈ X}. Akram and Nasir [5] defined interval-valued neutrosophic graph as follows: Definition 2.2. [5] An interval-valued neutrosophic graph on a nonempty set X is a pair G = (A, B), where A is an interval-valued neutrosophic set on X and B is an interval-valued neutrosophic relation on X such that: 1. t−B (xy) ≤ min(t−A (x), t−A(y)), 2. i−B (xy) ≤ min(i−A (x), i−A (y)), 3. fB− (xy) ≤ min( fA− (x), fA− (y)),
t+B (xy) ≤ min(t+A (x), t+A (y)), i+B (xy) ≤ min(i+A (x), i+A(y)), fB+ (xy) ≤ min( fA+ (x), fA+ (y)),
for all x, y ∈ X. Note that B is called symmetric relation on A. We now introduce the notion of an interval-valued neutrosophic line graph as a generalization of an interval-valued fuzzy line graph [1]. ˆ = (X, Y) be line graph of the crisp graph G ˆ = (V, E). Let A1 = ([t− , t+ ], [i− , i+ ], [ f − , f + ]) Definition 2.3. Let L(G) A1 A1 A1 A1 A1 A1 and B1 = ([t−B1 , t+B1 ], [i−B1 , i+B1 ], [ fB−1 , fB+1 ]) be interval-valued neutrosophic sets on V and E, A2 = ([t−A2 , t+A2 ], [i−A2 , i+A2 ], [ fA−2 , fA+2 ]) and B2 = ([t−B2 , t+B2 ], [i−B2 , i+B2 ], [ fB−2 , fB+2 ]) on X and Y, respectively. Then an interval-valued neutrosophic line graph of the interval-valued neutrosophic graph G = (A1 , B1 ) is an interval-valued neutrosophic graph L(G) = (A2 , B2 ) such that
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
58
(i) t−A2 (Sx ) = t−B1 (x) = t−B1 (ux vx ), t+A2 (Sx ) = t+B1 (x) = t+B1 (ux vx ), (ii) i−A2 (Sx ) = i−B1 (x) = i−B1 (ux vx ), i+A2 (Sx ) = i+B1 (x) = i+B1 (ux vx ), (iii) fA−2 (Sx ) = fB−1 (x) = fB−1 (ux vx ), fA+2 (Sx ) = fB+1 (x) = fB+1 (ux vx ), (iv) t−B2 (Sx S y ) = min(t−B1 (x), t−B1 (y)), t+B2 (Sx S y ) = min(t+B1 (x), t+B1 (y)), (v) i−B2 (Sx S y ) = min(i−B1 (x), i−B1 (y)), i+B2 (Sx S y ) = min(i+B1 (x), i+B1 (y)), (vi) fB−2 (Sx S y ) = min( fB−1 (x), fB−1 (y)), fB+2 (Sx S y ) = min( fB+1 (x), fB+1 (y)), for all Sx , S y ∈ X, Sx S y ∈ Y. Proposition 2.4. L(G) = (A2 , B2 ) is an interval-valued neutrosophic line graph of some interval-valued neutrosophic graph G = (A1 , B1 ) if and only if t−B2 (Sx S y ) = min(t−A2 (Sx ), t−A2 (S y )), t+B2 (Sx S y ) = min(t+A2 (Sx ), t+A2 (S y )), i−B2 (Sx S y ) = min(i−A2 (Sx ), i−A2 (S y )), i+B2 (Sx S y ) = min(i+A2 (Sx ), i+A2 (S y )), fB−2 (Sx S y ) = min( fA−2 (Sx ), fA−2 (S y )), fB+2 (Sx S y ) = min( fA+2 (Sx ), fA+2 (S y )), ∀Sx , S y ∈ Y. Proof. By using similar arguments as used in the proof of Proposition 3.7 of [1], the proof is straightforward. Definition 2.5. Consider two interval-valued neutrosophic graphs G1 = (A1 , B1 ) and G2 = (A2 , B2 ). A mapping ϕ : V1 → V2 is called homomorphism ϕ : G1 → G2 if ( − tA1 (x1 ) ≤ t−A2 (ϕ(x1)), i−A1 (x1 ) ≤ i−A2 (ϕ(x1 )), fA−1 (x1 ) ≤ fA−2 (ϕ(x1)), (a) t+A1 (x1 ) ≤ t+A2 (ϕ(x1)), i+A1 (x1 ) ≤ i+A2 (ϕ(x1 )), fA+1 (x1 ) ≤ fA+2 (ϕ(x1)), − t (x1 y1 ) ≤ t− (ϕ(x1)ϕ(y1 )), t+ (x1 y1 ) ≤ t+ (ϕ(x1 )ϕ(y1 )), i−B1(x y ) ≤ i−B2(ϕ(x )ϕ(y )), i+B1(x y ) ≤ i+B2(ϕ(x )ϕ(y )), (b) 1 1 1 1 B1 1 1 B2 B1 1 1 B2 f − (x1 y1 ) ≤ f − (ϕ(x1 )ϕ(y1 )), f + (x1 y1 ) ≤ f + (ϕ(x1)ϕ(y1 )), B1 B2 B1 B2
for all x1 ∈ V1 , x1 y1 ∈ E1 . Weak vertex-isomorphism of interval-valued neutrosophic graphs is a bijective homomorphism ϕ : G1 → G2 , such that ( − tA1 (x1 ) = t−A2 (ϕ(x1)), i−A1 (x1 ) = i−A2 (ϕ(x1 )), fA−1 (x1 ) = fA−2 (ϕ(x1 )), (c) t+A1 (x1 ) = t+A2 (ϕ(x1)), i+A1 (x1 ) = i+A2 (ϕ(x1 )), fA+1 (x1 ) = fA+2 (ϕ(x1 )), for all x1 (d)
∈ V1 and ϕ : G1 → G2 is called weak line-isomorphism if t−B1 (x1 y1 ) = t−B2 (ϕ(x1)ϕ(y1 )), t+B1 (x1 y1 ) = t+B2 (ϕ(x1 )ϕ(y1 )), i−B1 (x1 y1 ) = i−B2 (ϕ(x1 )ϕ(y1 )), i+B1 (x1 y1 ) = i+B2 (ϕ(x1 )ϕ(y1)), fB−1 (x1 y1 ) = fB−2 (ϕ(x1 )ϕ(y1 )), fB+1 (x1 y1 ) = fB+2 (ϕ(x1)ϕ(y1 )),
for all x1 y1 ∈ V1 . Weak isomorphism ϕ : G1 → G2 of two interval-valued neutrosophic graphs G1 and G2 is bijective homomorphism and satisfies (c) and (d). Weak isomorphism may not preserve the weights of the edges but preserves the weights of vertices . Theorem 2.6. Let L(G) = (A2 , B2 ) be an interval-valued neutrosophic line graph corresponding to an interval-valued neutrosophic graph G = (A1 , B1 ). Suppose that Gˆ = (V, E) is a connected graph. Then
59
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
(i) there is a week isomorphism between G and L(G) if and only if Gˆ is a cyclic graph and ∀ v ∈ V, x ∈ E, t−A1 (v) = t−B1 (x), i−A1 (v) = i−B1 (x), fA−1 (v) = fB−1 (x), t+A1 (v) = t+B1 (x), i+A1 (v) = i+B1 (x), fA+1 (v) = fB+1 (x), i.e., A1 = ([t−A1 , t+A1 ], [i−A1 , i+A1 ], [ fA−1 , fA+1 ]) and B1 = ([t−B1 , t+B1 ], [i−B1 , i+B1 ], [ fB−1 , fB+1 ]) are constant functions on the sets V and E, respectively, taking on same value. (ii) If ϕ is a weak isomorphism between G and L(G), then ϕ is an isomorphism. Proof. By using similar arguments as used in the proof of Theorem 3.11 of [1], the proof is straightforward. 3. Operations on I-V Neutrosophic Graph Structures In this section, we describe certain methods of construction of new interval-valued neutrosophic graph structures from old one. Definition 3.1. Gˇ iv = (I, I1 , I2 , . . . , It ) is called an interval-valued neutrosophic graph structure(IVNGS) of graph structure Gs = (U, U1 , U2 , . . . , Ut ) if I =< r, [t− (r), t+ (r)], [i− (r), i+ (r)], [ f − (r), f + (r)] > and I j =< rs, [t− (rs), t+ (rs)], [i− (rs), i+ (rs)], [ f − (rs), f + (rs)] > are interval-valued neutrosophic(IVN) sets on U and U j , respectively, such that: t+j (rs) ≤ min{t+ (r), t+ (s)}, − − − i j (rs) ≤ min{i (r), i (s)}, i+j (rs) ≤ min{i+ (r), i+ (s)}, f j− (rs) ≤ min{ f − (r), f − (s)}, f j+ (rs) ≤ min{ f + (r), f + (s)},
1. t−j (rs) ≤ min{t− (r), t− (s)}, 2. 3.
for all r, s ∈ U. Note that 0 ≤ t j (rs) + i j (rs) + f j (rs) ≤ 3, for all (rs) ∈ U j , j = 1, 2, . . . , t. Example 3.2. Consider graph structure Gs = (U, U1 , U2 ) such that U = {r1 , r2 , r3 , r4 , r5 , r6 }, U1 = {r1 r4 , r2 r4 , r2 r6 }, U2 = {r1 r5 , r3 r5 , r3 r6 }. Let I be an IVN set on U given in Table. 1 and I1 , I2 be IVN sets on U1 , U2 , respectively given in Table. 2. and Table. 3. Table 1: IVN set I on vertex set U
I t− t+ i− i+ f− f+
r1 0.2 0.3 0.3 0.4 0.4 0.5
Table 2: IVN set I1 on set U1
I1 t− t+ i− i+ f− f+
r1 r4 0.1 0.2 0.3 0.4 0.2 0.3
r2 r4 0.1 0.2 0.4 0.5 0.2 0.3
r2 r6 0.3 0.4 0.1 0.2 0.3 0.4
r2 0.3 0.4 0.4 0.5 0.3 0.4
r3 0.3 0.4 0.4 0.5 0.3 0.4
r4 0.1 0.2 0.4 0.5 0.2 0.3
r5 0.3 0.4 0.4 0.5 0.3 0.4
r6 0.3 0.4 0.1 0.2 0.3 0.4
Table 3: IVN set I2 on set U2
I2 t− t+ i− i+ f− f+
r1 r5 0.2 0.3 0.3 0.4 0.3 0.4
r3 r5 0.3 0.4 0.4 0.5 0.3 0.4
r3 r6 0.3 0.4 0.1 0.2 0.3 0.4
Routine calculations show that Gˇ iv = (I, I1, I2 ) is an interval-valued neutrosophic graph structure, as shown in Fig. 1.
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80 r2 ([0.3, 0.4], [0.4, 0.5], [0.3, 0.4])
.3 ,
], [ ,0 ) 0.4 ] , [0 ,0 .5]
0.4
])
0 .4 ], [ 0 .4
.2 .3
], [ .3 , [0
] .4 )
3 0. 2,
r6 (
,0
. [0 ],
3 0.
0 .4
,[
.5 ,0
] .4
.4
0 .1
I2 (
b
,0
[0
.3
],
[0
.2
b
[0
],
,0
.3 ,
,0
.1
b
.2] , [0 .3 ,
], [ 0 .2 1, [0 .
[0
I1 (
.3,
])
0 .4
,0
0.4
.5]
, [0
.3 , , [0
.2,
.2]
b
,0
0 .3 ])
0 .1
b
]) 0.4 .3, , [0 .5] ,0 0 .4 ], [ 0.4]) 0.4 I2 ([0.3, 0.4], [0.1, 0.2], [0.3,
0 .4 b
I 2(
([0 r4
I1 ([0.1, 0.2], [0.3, 0.4], [0.2, 0.3])
([0 r3
.3 ,
,[
[0
.2
3]
I 1(
([0 r1
. ,0
3 0.
[0
], .4 ,0
]) .5 ,0 4 .
])
r5 ([0.3, 0.4], [0.4, 0.5], [0.3, 0.4]) Figure 1: An IVNGS Gˇ iv = (I, I1 , I2 )
We now present some operations on IVNGSs. Definition 3.3. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs of graph structures Gs1 = (U1 , U11 , U12 , . . . , U1t ) and Gs2 = (U2 , U21 , U22 , . . . , U2t ), respectively. Cartesian product of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 × Gˇ iv2 = (I1 × I2 , I11 × I21 , I12 × I22 , . . . , I1t × I2t ), is defined as: − t(I ×I ) (rs) = (t−I × t−I )(rs) = t−I (r) ∧ t−I (s) i− 1 2 (rs) = (i−1 × i−2)(rs) = i−1(r) ∧ i− 2(s) (i) I1 I2 I1 I2 (I1 ×I2 ) f − (rs) = ( f − × f − )(rs) = f − (r) ∧ f − (s) I1 I2 I1 I2 (I1 ×I2 )
+ t(I ×I ) (rs) = (t+I × t+I )(rs) = t+I (r) ∧ t+I (s) i+ 1 2 (rs) = (i+1 × i+2)(rs) = i+1(r) ∧ i+ 2(s) (ii) I1 I2 I1 I2 (I1 ×I2 ) f(I+ ×I ) (rs) = ( fI+ × fI+ )(rs) = fI+ (r) ∧ fI+ (s) 1 2 1 2 1 2 for all rs ∈ U1 × U2 , − t(I1 j ×I2 j ) (rs1 )(rs2 ) = (t−I1 j × t−I2 j )(rs1 )(rs2 ) = t−I1 (r) ∧ t−I2 j (s1 s2 ) i− (rs1 )(rs2 ) = (i−I1 j × i−I2 j )(rs1 )(rs2 ) = i−I1 (r) ∧ i−I2 j (s1 s2 ) (iii) (I−1 j ×I2 j ) f (rs1 )(rs2 ) = ( fI−1 j × fI−2 j )(rs1 )(rs2 ) = fI−1 (r) ∧ fI−2 j (s1 s2 ) (I1 j ×I2 j )
+ t(I1 j ×I2 j ) (rs1 )(rs2 ) = (t+I1 j × t+I2 j )(rs1 )(rs2 ) = t+I1 (r) ∧ t+I2 j (s1 s2 ) i+ (rs1 )(rs2 ) = (i+I1 j × i+I2 j )(rs1 )(rs2 ) = i+I1 (r) ∧ i+I2 j (s1 s2 ) (iv) (I1 j ×I2 j ) + f (rs1 )(rs2 ) = ( fI+1 j × fI+2 j )(rs1 )(rs2 ) = fI+1 (r) ∧ fI+2 j (s1 s2 ) (I1 j ×I2 j ) for all r ∈ U1 , s1 s2 ∈ U2 j , − t(I1 j ×I2 j ) (r1 s)(r2 s) = (t−I1 j × t−I2 j )(r1 s)(r2 s) = t−I2 (s) ∧ t−I1 j (r1 r2 ) i− (r1 s)(r2 s) = (i−I1 j × i−I2 j )(r1 s)(r2 s) = i−I2 (s) ∧ i−I2 j (r1 r2 ) (v) (I−1 j ×I2 j ) f (r s)(r2 s) = ( fI−1 j × fI−2 j )(r1 s)(r2 s) = fI−2 (s) ∧ fI−2 j (r1 r2 ) (I1 j ×I2 j ) 1
60
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
+ t(I1 j ×I2 j ) (r1 s)(r2 s) = (t+I1 j × t+I2 j )(r1 s)(r2 s) = t+I2 (s) ∧ t+I1 j (r1 r2 ) i+ (r s)(r2 s) = (i+I1 j × i+I2 j )(r1 s)(r2 s) = i+I2 (s) ∧ i+I2 j (r1 r2 ) (vi) (I1 j ×I2 j ) 1 + f (r s)(r2 s) = ( fI+1 j × fI+2 j )(r1 s)(r2 s) = fI+2 (s) ∧ fI+2 j (r1 r2 ) (I1 j ×I2 j ) 1 for all s ∈ U2 , r1 r2 ∈ U1 j , j = 1, 2, . . . , t.
Example 3.4. Consider Gˇ iv1 = (I1 , I11 , I12 ) and Gˇ iv2 = (I2 , I21 , I22 ) are two IVNGSs of graph structures Gˇ s1 = (U1 , U11 , U12 ) and Gˇ s2 = (U2 , U21 , U22 ), respectively, as shown in Fig. 2, where U11 = {r1 r2 }, U12 = {r3 r4 }, U21 = {s1 s2 }, U22 = {s2 s3 }.
r1 ([0.5, 0.6], [0.2, 0.3], [0.6, 0.7]) b
r3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5]) b
I12 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5]) I11 ([0.5, 0.6], [0.2, 0.3], [0.6, 0.7])
b b
r4 ([0.4, 0.5], [0.3, 0.4], [0.6, 0.7])
r2 ([0.5, 0.6], [0.3, 0.4], [0.8, 0.9])
[0 . I 21(
2, 0
.3 ] ,
s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) ]) , 0.4 b [0.3 , ] 3 , 0. [ 0 .2
b
s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
Gˇ iv1 = (I1 , I11 , I12 )
I22 ([
0 .3 ,
0 .4 ] ,
[ 0 .3 ,
0.4], [
b 0.4, 0.5])
s3 ([0.5, 0.6], [0.4, 0.5], [0.5, 0.6]) Gˇ iv2 = (I2 , I21 , I22 ) Figure 2: Two IVNGSs Gˇ iv1 and Gˇ iv2
Cartesian product of Gˇ iv1 and Gˇ iv2 defined as Gˇ iv1 × Gˇ iv2 = {I1 × I2 , I11 × I21 , I12 × I22 } is shown in Fig. 3 and Fig. 4.
61
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
62
r1 s3 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6]) r1 s2 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5]) I12 × I22 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5]) b
I1
1
×
I11
I2
1(
[0
.2 ,
0 .3
], [
0 .2
I1
1
×I
21 ([ 0
,0 .3]
, [0
.3,
.3 , 0
0.4 ]
×
I2
1(
.4 ] ,
[ 0 .2
, 0.3
], [0 .
[0
4, 0 .5
.2 ,
b
0 .3
], [
0 .2
])
,0
.3]
, [0
.3,
)
0.4 ]
) b
b b
r1 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
I11 × I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r2 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) b
I12 × I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r2 s3 ([0.5, 0.6], [0.3, 0.4], [0.5, 0.6]) r2 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
Figure 3: Gˇ iv1 × Gˇ iv2
r3 s3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5]) r3 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) I12 × I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I1
1
×
I2
1(
b
b
b
I12 [0
.2 ,
0 .3
], [
0 .2
I1
1
×I
22 ([ 0
,0 .3 ] , [0
.3,
.3 , 0
0.4 ])
×
I2
1 ([
.4 ] ,
[ 0 .3
, 0.4
], [0 .
0 .2
4, 0 .5
,0
])
.3 ]
, [0
.2 ,
0 .3 ], [
0.3 ,
0 .4 ])
b
r3 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
b
I12 × I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r4 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) b
I12 × I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r4 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r4 s3 ([0.4, 0.5], [0.3, 0.4], [0.5, 0.6])
Figure 4: Gˇ iv1 × Gˇ iv2
Theorem 3.5. Cartesian product Gˇ iv1 × Gˇ iv2 = (I1 × I2 , I11 × I21 , I12 × I22 , . . . , I1t × I2t ) of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively is an IVNGS of Gs1 × Gs2 . Definition 3.6. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs. Cross product of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 ∗ Gˇ iv2 = (I1 ∗ I2 , I11 ∗ I21 , I12 ∗ I22 , . . . , I1t ∗ I2t ), is defined as: − t (rs) = (t−I1 ∗ t−I2 )(rs) = t−I1 (r) ∧ t−I2 (s) −(I1 ∗I2 ) i(I1 ∗I2 ) (rs) = (i−I1 ∗ i−I2 )(rs) = i−I1 (r) ∧ i−I2 (s) (i) f(I− ∗I ) (rs) = ( fI− ∗ fI− )(rs) = fI− (r) ∧ fI− (s) 1 2 1 2 1 2
+ t(I1 ∗I2 ) (rs) = (t+I1 ∗ t+I2 )(rs) = t+I1 (r) ∧ t+I2 (s) i+ (rs) = (i+ ∗ i+ )(rs) = i+ (r) ∧ i+ (s) (ii) I1 I2 I1 I2 (I1 ∗I2 ) f(I+ ∗I ) (rs) = ( fI+ ∗ fI+ )(rs) = fI+ (r) ∧ fI− (s) 1 2 1 2 1 2 for all (rs) ∈ U1 × U2 ,
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
− t(I1 j ∗I2 j ) (r1 s1 )(r2 s2 ) = (t−I1 j ∗ t−I2 j )(r1 s1 )(r2 s2 ) = t−I1 j (r1 r2 ) ∧ t−I2 j (s1 s2 ) i− (r s )(r2 s2 ) = (i−I1 j ∗ i−I2 j )(r1 s1 )(r2 s2 ) = i−I1 j (r1 r2 ) ∧ i−I2 j (s1 s2 ) (iii) (I1 j ∗I2 j ) 1 1 − f (r s )(r2 s2 ) = ( fI−1 j ∗ fI−2 j )(r1 s1 )(r2 s2 ) = fI−1 j (r1 r2 ) ∧ fI−2 j (s1 s2 ) (I1 j ∗I2 j ) 1 1
+ t(I1 j ∗I2 j ) (r1 s1 )(r2 s2 ) = (t+I1 j ∗ t+I2 j )(r1 s1 )(r2 s2 ) = t+I1 j (r1 r2 ) ∧ t+I2 j (s1 s2 ) i+ (r s )(r2 s2 ) = (i+I1 j ∗ i+I2 j )(r1 s1 )(r2 s2 ) = i+I1 j (r1 r2 ) ∧ i+I2 j (s1 s2 ) (iv) (I1 j ∗I2 j ) 1 1 f+ (r s )(r2 s2 ) = ( fI+1 j ∗ fI+2 j )(r1 s1 )(r2 s2 ) = fI+1 j (r1 r2 ) ∧ fI+2 j (s1 s2 ) (I1 j ∗I2 j ) 1 1 for all r1 r2 ∈ U1 j , s1 s2 ∈ U2 j .
Example 3.7. Cross product of IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 ∗ Gˇ iv2 = {I1 ∗ I2 , I11 ∗ I21 , I12 ∗ I22 } and is shown in Fig. 5 and Fig. 6. r1 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r1 s3 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6])
r1 s2 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5]) b
b b
I11 ∗ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) I11 ∗ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
b b
b
r2 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r2 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r2 s3 ([0.5, 0.6], [0.3, 0.4], [0.5, 0.6]) Figure 5: Gˇ iv1 ∗ Gˇ iv2
r3 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r3 s3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
r3 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) b
b b
I12 ∗ I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I12 ∗ I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
b b
b
r4 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r4 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) r4 s3 ([0.4, 0.5], [0.3, 0.4], [0.5, 0.6]) Figure 6: Gˇ iv1 ∗ Gˇ iv2
Theorem 3.8. Cross product Gˇ iv1 ∗ Gˇ iv2 = (I1 ∗ I2 , I11 ∗ I21 , I12 ∗ I22 , . . . , I1t ∗ I2t ) of two IVNGSs of graph structures Gs1 and Gs2 is an IVNGS of Gs1 ∗ Gs2 . Definition 3.9. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs. Lexicographic product of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 • Gˇ iv2 = (I1 • I2 , I11 • I21 , I12 • I22 , . . . , I1t • I2t ), is defined as:
63
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
− t(I •I ) (rs) = (t−I • t−I )(rs) = t−I (r) ∧ t−I (s) i− 1 2 (rs) = (i−1 • i−2)(rs) = i−1(r) ∧ i− 2(s) (i) I1 I2 I1 I2 (I1 •I2 ) f(I− •I ) (rs) = ( fI− • fI− )(rs) = fI− (r) ∧ fI− (s) 1 2 1 2 1 2
+ t(I •I ) (rs) = (t+I • t+I )(rs) = t+I (r) ∧ t+I (s) i+ 1 2 (rs) = (i+1 • i+2)(rs) = i+1(r) ∧ i+ 2(s) (ii) I1 I2 I1 I2 (I1 •I2 ) f(I+ •I ) (rs) = ( fI+ • fI+ )(rs) = fI+ (r) ∧ fI+ (s) 1 2 1 2 1 2 for all rs ∈ U1 × U2 , − t(I1 j •I2 j ) (rs1 )(rs2 ) = (t−I1 j • t−I2 j )(rs1 )(rs2 ) = t−I1 (r) ∧ t−I2 j (s1 s2 ) i− (rs1 )(rs2 ) = (i−I1 j • i−I2 j )(rs1 )(rs2 ) = i−I1 (r) ∧ i−I2 j (s1 s2 ) (iii) (I1 j •I2 j ) f− (rs1 )(rs2 ) = ( fI−1 j • fI−2 j )(rs1 )(rs2 ) = fI−1 (r) ∧ fI−2 j (s1 s2 ) (I1 j •I2 j )
+ t(I1 j •I2 j ) (rs1 )(rs2 ) = (t+I1 j • t+I2 j )(rs1 )(rs2 ) = t+I1 (r) ∧ t+I2 j (s1 s2 ) i+ (rs1 )(rs2 ) = (i+I1 j • i+I2 j )(rs1 )(rs2 ) = i+I1 (r) ∧ i+I2 j (s1 s2 ) (iv) (I1 j •I2 j ) f+ (rs1 )(rs2 ) = ( fI+1 j • fI+2 j )(rs1 )(rs2 ) = fI+1 (r) ∧ fI+2 j (s1 s2 ) (I1 j •I2 j ) for all r ∈ U1 , s1 s2 ∈ U2 j , − t(I1 j •I2 j ) (r1 s1 )(r2 s2 ) = (t−I1 j • t−I2 j )(r1 s1 )(r2 s2 ) = t−I1 j (r1 r2 ) ∧ t−I2 j (s1 s2 ) i− (r s )(r2 s2 ) = (i−I1 j • i−I2 j )(r1 s1 )(r2 s2 ) = i−I1 j (r1 r2 ) ∧ i−I2 j (s1 s2 ) (v) (I1 j •I2 j ) 1 1 − f (r s )(r2 s2 ) = ( fI−1 j • fI−2 j )(r1 s1 )(r2 s2 ) = fI−1 j (r1 r2 ) ∧ fI−2 j (s1 s2 ) (I1 j •I2 j ) 1 1
+ t(I1 j •I2 j ) (r1 s1 )(r2 s2 ) = (t+I1 j • t+I2 j )(r1 s1 )(r2 s2 ) = t+I1 j (r1 r2 ) ∧ t+I2 j (s1 s2 ) i+ (r s )(r2 s2 ) = (i+I1 j • i+I2 j )(r1 s1 )(r2 s2 ) = i+I1 j (r1 r2 ) ∧ i+I2 j (s1 s2 ) (vi) (I1 j •I2 j ) 1 1 f+ (r s )(r2 s2 ) = ( fI+1 j • fI+2 j )(r1 s1 )(r2 s2 ) = fI+1 j (r1 r2 ) ∧ fI+2 j (s1 s2 ) (I1 j •I2 j ) 1 1 for all r1 r2 ∈ U1 j , s1 s2 ∈ U2 j . Example 3.10. Lexicographic product of IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 • Gˇ iv2 = {I1 • I2 , I11 • I21 , I12 • I22 } and is depicted in Fig. 7 and Fig. 8.
I11 • I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r1 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) b
. ,0 .2 ([0
I 11 I1
1
•
•
b
r1 s2 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
I 21
I2
1(
, 3] 0. 2, . , [0 b 3]
) 4] 0. 3, . [0
r2 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r2 s3 ([0.5, 0.6], [0.3, 0.4], [0.5, 0.6])
]) 0.4 b ) .3, 0 5] [ , 0. 4, .3] . 0 , [0 ], 0.2 .4 ], [ ,0 3 3 . . 0 0 .2, ], [ .4 ([0 ,0 21 I 3 . • ([0 I 11 I 22 • I 12
[0 .2 ,0 .3 ], b [0 .2 ,0 .3 ], [0 .3 ,0 .4 ])
r2 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) b
r1 s3 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6]) I12 • I22 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
Figure 7: Gˇ iv1 • Gˇ iv2
64
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
65
r4 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) ) I11 • I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) 5]
b b
r3 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
I12 • I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
]) 0.4
I 11 I1
1
•
•I
I2
21
1(
[0 .3 ,0 .4 ], [0 .3 ,0 .4 ], [0 .4 ,0 .5 ]) b
b
b
, 0.3 ], [ 0.3
[0.4, 0.5])
I 11
.2, ([0 21 I •
, 0.2 ], [ 3 . 0
.3, , [0 .4] 0 .3, ([0 b
r4 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
I11 • I21 ([0.3, 0.4], [0.3, 0.4],
r3 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
0. .4, , [0 ] 4 0.
r3 s3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5]) r4 s3 ([0.4, 0.5], [0.3, 0.4], [0.5, 0.6])
Figure 8: Gˇ iv1 • Gˇ iv2
Theorem 3.11. Lexicographic product Gˇ iv1 • Gˇ iv2 = (I1 • I2 , I11 • I21 , I12 • I22 , . . . , I1t • I2t ) of two IVNGSs of graph structures Gs1 and Gs2 is an IVNGS of Gs1 • Gs2 . Proof. Consider two cases: Case 1. For r ∈ U1 , s1 s2 ∈ U2 j , t−(I1 j •I2 j ) ((rs1 )(rs2 )) = t−I1 (r) ∧ t−I2 j (s1 s2 ) ≤ t−I1 (r) ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r) ∧ t−I2 (s1 )] ∧ [t−I1 (r) ∧ t−I2 (s2 )] = t−(I1 •I2 ) (rs1 ) ∧ t−(I1 •I2 ) (rs2 ), t+(I1 j •I2 j ) ((rs1 )(rs2 )) = t+I1 (r) ∧ t+I2 j (s1 s2 ) ≤ t+I1 (r) ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r) ∧ t+I2 (s1 )] ∧ [t+I1 (r) ∧ t+I2 (s2 )] = t+(I1 •I2 ) (rs1 ) ∧ t+(I1 •I2 ) (rs2 ),
i−(I1 j •I2 j ) ((rs1 )(rs2 )) = i−I1 (r) ∧ i−I2 j (s1 s2 ) ≤ i−I1 (r) ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r) ∧ i−I2 (s1 )] ∧ [i−I1 (r) ∧ i−I2 (s2 )] = i−(I1 •I2 ) (rs1 ) ∧ i−(I1 •I2 ) (rs2 ), i+(I1 j •I2 j ) ((rs1 )(rs2 )) = i+I1 (r) ∧ i+I2 j (s1 s2 ) ≤ i+I1 (r) ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r) ∧ i+I2 (s1 )] ∧ [i+I1 (r) ∧ i+I2 (s2 )] = i+(I1 •I2 ) (rs1 ) ∧ i+(I1 •I2 ) (rs2 ),
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
f(I−1 j •I2 j ) ((rs1 )(rs2 )) = fI−1 (r) ∧ fI−2 j (s1 s2 ) ≤ fI−1 (r) ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r) ∧ fI−2 (s1 )] ∧ [ fI−1 (r) ∧ fI−2 (s2 )] = f(I−1 •I2 ) (rs1 ) ∧ f(I−1 •I2 ) (rs2 ), f(I+1 j •I2 j ) ((rs1 )(rs2 )) = fI+1 (r) ∧ fI+2 j (s1 s2 ) ≤ fI+1 (r) ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r) ∧ fI+2 (s1 )] ∧ [ fI+1 (r) ∧ fI+2 (s2 )] = f(I+1 •I2 ) (rs1 ) ∧ f(I+1 •I2 ) (rs2 ), for rs1 , rs2 ∈ U1 • U2 . Case 2. For r1 r2 ∈ U1 j , s1 s2 ∈ U2 j , t−(I1 j •I2 j ) ((r1 s1 )(r2 s2 )) = t−I1 j (r1 r2 ) ∧ t−I2 j (s1 s2 ) ≤ [t−I1 (r1 ) ∧ t−I1 (r2 ] ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r1 ) ∧ t−I2 (s1 )] ∧ [t−I1 (r2 ) ∧ t−I2 (s2 )] = t−(I1 •I2 ) (r1 s1 ) ∧ t−(I1 •I2 ) (r2 s2 ), t+(I1 j •I2 j ) ((r1 s1 )(r2 s2 )) = t+I1 j (r1 r2 ) ∧ t+I2 j (s1 s2 ) ≤ [t+I1 (r1 ) ∧ t+I1 (r2 ] ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r1 ) ∧ t+I2 (s1 )] ∧ [t+I1 (r2 ) ∧ t+I2 (s2 )] = t+(I1 •I2 ) (r1 s1 ) ∧ t+(I1 •I2 ) (r2 s2 ), i−(I1 j •I2 j ) ((r1 s1 )(r2 s2 )) = i−I1 j (r1 r2 ) ∧ i−I2 j (s1 s2 ) ≤ [i−I1 (r1 ) ∧ i−I1 (r2 ] ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r1 ) ∧ i−I2 (s1 )] ∧ [i−I1 (r2 ) ∧ i−I2 (s2 )] = i−(I1 •I2 ) (r1 s1 ) ∧ i−(I1 •I2 ) (r2 s2 ), i+(I1 j •I2 j ) ((r1 s1 )(r2 s2 )) = i+I1 j (r1 r2 ) ∧ i+I2 j (s1 s2 ) ≤ [i+I1 (r1 ) ∧ i+I1 (r2 ] ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r1 ) ∧ i+I2 (s1 )] ∧ [i+I1 (r2 ) ∧ i+I2 (s2 )] = i+(I1 •I2 ) (r1 s1 ) ∧ i+(I1 •I2 ) (r2 s2 ), f(I−1 j •I2 j ) ((r1 s1 )(r2 s2 )) = fI−1 j (r1 r2 ) ∧ fI−2 j (s1 s2 ) ≤ [ fI−1 (r1 ) ∧ fI−1 (r2 ] ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r1 ) ∧ fI−2 (s1 )] ∧ [ fI−1 (r2 ) ∧ fI−2 (s2 )] = f(I−1 •I2 ) (r1 s1 ) ∧ f(I−1 •I2 ) (r2 s2 ),
66
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
f(I+1 j •I2 j ) ((r1 s1 )(r2 s2 )) = fI+1 j (r1 r2 ) ∧ fI+2 j (s1 s2 ) ≤ [ fI+1 (r1 ) ∧ fI+1 (r2 ] ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r1 ) ∧ fI+2 (s1 )] ∧ [ fI+1 (r2 ) ∧ fI+2 (s2 )] = f(I+1 •I2 ) (r1 s1 ) ∧ f(I+1 •I2 ) (r2 s2 ), r1 s1 , r2 s2 ∈ U1 • U2 and j ∈ {1, 2, . . . , t}. This completes the proof. Definition 3.12. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs. Strong product of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 ⊠ Gˇ iv2 = (I1 ⊠ I2 , I11 ⊠ I21 , I12 ⊠ I22 , . . . , I1t ⊠ I2t ), is defined as: − t(I1 ⊠I2 ) (rs) = (t−I1 ⊠ t−I2 )(rs) = t−I1 (r) ∧ t−I2 (s) i− (rs) = (i−I1 ⊠ i−I2 )(rs) = i−I1 (r) ∧ i−I2 (s) (i) (I1 ⊠I2 ) − f(I ⊠I ) (rs) = ( fI− ⊠ fI− )(rs) = fI− (r) ∧ fI− (s) 1 2 1 2 1 2 + t(I ⊠I ) (rs) = (t+I ⊠ t+I )(rs) = t+I (r) ∧ t+I (s) i+ 1 2 (rs) = (i+1 ⊠ i+2)(rs) = i+1(r) ∧ i+ 2(s) (ii) I1 I2 I1 I2 (I1 ⊠I2 ) f + (rs) = ( f + ⊠ f + )(rs) = f + (r) ∧ f − (s) I1 I2 I1 I2 (I1 ⊠I2 ) for all rs ∈ U1 × U2 , − t(I1 j ⊠I2 j ) (rs1 )(rs2 ) = (t−I1 j ⊠ t−I2 j )(rs1 )(rs2 ) = t−I1 (r) ∧ t−I2 j (s1 s2 ) i− (rs1 )(rs2 ) = (i−I1 j ⊠ i−I2 j )(rs1 )(rs2 ) = i−I1 (r) ∧ i−I2 j (s1 s2 ) (iii) (I−1 j ⊠I2 j ) f (rs1 )(rs2 ) = ( fI−1 j ⊠ fI−2 j )(rs1 )(rs2 ) = fI−1 (r) ∧ fI−2 j (s1 s2 ) (I1 j ⊠I2 j )
+ t(I1 j ⊠I2 j ) (rs1 )(rs2 ) = (t+I1 j ⊠ t+I2 j )(rs1 )(rs2 ) = t+I1 (r) ∧ t+I2 j (s1 s2 ) i+ (rs1 )(rs2 ) = (i+I1 j ⊠ i+I2 j )(rs1 )(rs2 ) = i+I1 (r) ∧ i+I2 j (s1 s2 ) (iv) (I1 j ⊠I2 j ) + f (rs1 )(rs2 ) = ( fI+1 j ⊠ fI+2 j )(rs1 )(rs2 ) = fI+1 (r) ∧ fI+2 j (s1 s2 ) (I1 j ⊠I2 j ) for all r ∈ U1 , s1 s2 ∈ U2 j , − t(I1 j ⊠I2 j ) (r1 s)(r2 s) = (t−I1 j ⊠ t−I2 j )(r1 s)(r2 s) = t−I2 (s) ∧ t−I1 j (r1 r2 ) i− (r1 s)(r2 s) = (i−I1 j ⊠ i−I2 j )(r1 s)(r2 s) = i−I2 (s) ∧ i−I2 j (r1 r2 ) (v) (I−1 j ⊠I2 j ) f (r s)(r2 s) = ( fI−1 j ⊠ fI−2 j )(r1 s)(r2 s) = fI−2 (s) ∧ fI−2 j (r1 r2 ) (I1 j ⊠I2 j ) 1
+ t(I1 j ⊠I2 j ) (r1 s)(r2 s) = (t+I1 j ⊠ t+I2 j )(r1 s)(r2 s) = t+I2 (s) ∧ t+I1 j (r1 r2 ) i+ (r s)(r2 s) = (i+I1 j ⊠ i+I2 j )(r1 s)(r2 s) = i+I2 (s) ∧ i+I2 j (r1 r2 ) (vi) (I1 j ⊠I2 j ) 1 + f (r s)(r2 s) = ( fI+1 j ⊠ fI+2 j )(r1 s)(r2 s) = fI+2 (s) ∧ fI+2 j (r1 r2 ) (I1 j ⊠I2 j ) 1 for all s ∈ U2 , r1 r2 ∈ U1 j . − t (r1 s1 )(r2 s2 ) = (t−I1 j ⊠ t−I2 j )(r1 s1 )(r2 s2 ) = t−I1 j (r1 r2 ) ∧ t−I2 j (s1 s2 ) −(I1 j ⊠I2 j ) i(I1 j ⊠I2 j ) (r1 s1 )(r2 s2 ) = (i−I1 j ⊠ i−I2 j )(r1 s1 )(r2 s2 ) = i−I1 j (r1 r2 ) ∧ i−I2 j (s1 s2 ) (vii) f− (r s )(r2 s2 ) = ( fI−1 j ⊠ fI−2 j )(r1 s1 )(r2 s2 ) = fI−1 j (r1 r2 ) ∧ fI−2 j (s1 s2 ) (I1 j ⊠I2 j ) 1 1
+ t(I1 j ⊠I2 j ) (r1 s1 )(r2 s2 ) = (t+I1 j ⊠ t+I2 j )(r1 s1 )(r2 s2 ) = t+I1 j (r1 r2 ) ∧ t+I2 j (s1 s2 ) i+ (r s )(r2 s2 ) = (i+I1 j ⊠ i+I2 j )(r1 s1 )(r2 s2 ) = i+I1 j (r1 r2 ) ∧ i+I2 j (s1 s2 ) (viii) (I1 j ⊠I2 j ) 1 1 + f (r s )(r2 s2 ) = ( fI+1 j ⊠ fI+2 j )(r1 s1 )(r2 s2 ) = fI+1 j (r1 r2 ) ∧ fI+2 j (s1 s2 ) (I1 j ⊠I2 j ) 1 1 for all r1 r2 ∈ U1 j , s1 s2 ∈ U2 j .
67
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
68
Example 3.13. Strong product of IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 ⊠ Gˇ iv2 = {I1 ⊠ I2 , I11 ⊠ I21 , I12 ⊠ I22 } and is represented in Fig. 9 and Fig. 10. r2 s3 ([0.5, 0.6], [0.3, 0.4], [0.5, 0.6]) r1 s2 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
b
b
. ,0 .2 ([0
I 11
I1
1
⊠
⊠
. ,0 .2 0 [ , 3]
I 21
I2
1(
[0 .2 ,0 .3 b b ], [ 0. 2, I11 ⊠ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) 0.
r2 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
, 4] 0. 3, 0. [ ], .4 ,0 .3 0 ([ b
I 12 I1
2
⊠
⊠
I2
I 22
2(
3] ,[ 0. 3, 0. 4] )
) 5] 0. 4, . [0 I11 ⊠ I21 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6])
I11 ⊠ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
]) .4 ,0 .3 0 ,[ 3] I11 ⊠ I21 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
I11 ⊠ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r1 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
[0 .3 ,0 .4 ], b [0. 2, 0. 3] ,[ 0. 4, 0. 5] )
r2 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) r1 s3 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6])
Figure 9: Gˇ iv1 ⊠ Gˇ iv2
r3 s3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
r3 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
1
⊠
I 21
I2
1(
[0 .2 ,0 .3 ], [0 .2 ,0 .3 ], r3 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) [0 .3 ,0 .4 ])
I1
I1
2
⊠
I2
2
⊠
2(
[0 .3 ,0 .4 [0 ], .3 [0 ,0 .3 .4 ,0 ], .4 [0 ], .3 [0 ,0 .4 .4 ,0 ], .5 [0 ]) .4 ,0 .5 ])
2(
b
b
r4 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I2
I12 ⊠ I22 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
I1
⊠
I12 ⊠ I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I12 ⊠ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
b
b
I 11
]) 0.5 ) .4, 0 5] [ , 0. 4, .4] . 0 , [0 ], 0.3 .4 ], [ ,0 4 3 . . 0 [0 .3, ], .4 ([0 ,0 3 I 22 . ⊠ ([0 I 12 I 22 ⊠ I 12
b
, 0.2 ], [ 3 . 0 .2, ([0
]) 0.4
b
r4 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
, 0.3 ], [ 0.3
r4 s3 ([0.4, 0.5], [0.3, 0.4], [0.5, 0.6])
Figure 10: Gˇ iv1 ⊠ Gˇ iv2
Theorem 3.14. Strong product Gˇ iv1 ⊠ Gˇ iv2 = (I1 ⊠ I2 , I11 ⊠ I21 , I12 ⊠ I22 , . . . , I1t ⊠ I2t ) of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively is an IVNGS of Gs1 ⊠ Gs2 . Proof. Consider three cases:
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
Case 1. For r ∈ U1 , s1 s2 ∈ U2 j , t−(I1 j ⊠I2 j ) ((rs1 )(rs2 )) = t−I1 (r) ∧ t−I2 j (s1 s2 ) ≤ t−I1 (r) ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r) ∧ t−I2 (s1 )] ∧ [t−I1 (r) ∧ t−I2 (s2 )] = t−(I1 ⊠I2 ) (rs1 ) ∧ t−(I1 ⊠I2 ) (rs2 ), t+(I1 j ⊠I2 j ) ((rs1 )(rs2 )) = t+I1 (r) ∧ t+I2 j (s1 s2 ) ≤ t+I1 (r) ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r) ∧ t+I2 (s1 )] ∧ [t+I1 (r) ∧ t+I2 (s2 )] = t+(I1 ⊠I2 ) (rs1 ) ∧ t+(I1 ⊠I2 ) (rs2 ),
i−(I1 j ⊠I2 j ) ((rs1 )(rs2 )) = i−I1 (r) ∧ i−I2 j (s1 s2 ) ≤ i−I1 (r) ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r) ∧ i−I2 (s1 )] ∧ [i−I1 (r) ∧ i−I2 (s2 )] = i−(I1 ⊠I2 ) (rs1 ) ∧ i−(I1 ⊠I2 ) (rs2 ), i+(I1 j ⊠I2 j ) ((rs1 )(rs2 )) = i+I1 (r) ∧ i+I2 j (s1 s2 ) ≤ i+I1 (r) ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r) ∧ i+I2 (s1 )] ∧ [i+I1 (r) ∧ i+I2 (s2 )] = i+(I1 ⊠I2 ) (rs1 ) ∧ i+(I1 ⊠I2 ) (rs2 ),
f(I−1 j ⊠I2 j ) ((rs1 )(rs2 )) = fI−1 (r) ∧ fI−2 j (s1 s2 ) ≤ fI−1 (r) ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r) ∧ fI−2 (s1 )] ∧ [ fI−1 (r) ∧ fI−2 (s2 )] = f(I−1 ⊠I2 ) (rs1 ) ∧ f(I−1 ⊠I2 ) (rs2 ), f(I+1 j ⊠I2 j ) ((rs1 )(rs2 )) = fI+1 (r) ∧ fI+2 j (s1 s2 ) ≤ fI+1 (r) ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r) ∧ fI+2 (s1 )] ∧ [ fI+1 (r) ∧ fI+2 (s2 )] = f(I+1 ⊠I2 ) (rs1 ) ∧ f(I+1 ⊠I2 ) (rs2 ), for rs1 , rs2 ∈ U1 ⊠ U2 . Case 2. For r ∈ U2 , s1 s2 ∈ U1 j , t−(I1 j ⊠B2 j ) ((s1 r)(s2 r)) = t−I2 (r) ∧ t−I1 j (s1 s2 ) ≤ t−I2 (r) ∧ [t−I1 (s1 ) ∧ t−I1 (s2 )] = [t−I2 (r) ∧ t−I1 (s1 )] ∧ [t−I2 (r) ∧ t−I1 (s2 )] = t−(I1 ⊠I2 ) (s1 r) ∧ t−(I1 ⊠I2 ) (s2 r),
69
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
t+(I1 j ⊠I2 j ) ((s1 r)(s2 r)) = t+I2 (r) ∧ t+I1 j (s1 s2 ) ≤ t+I2 (r) ∧ [t+I1 (s1 ) ∧ t+I1 (s2 )] = [t+I2 (r) ∧ t+I1 (s1 )] ∧ [t+I2 (r) ∧ t+I1 (s2 )] = t+(I1 ⊠I2 ) (s1 r) ∧ t+(I1 ⊠I2 ) (s2 r), i−(I1 j ⊠I2 j ) ((s1 r)(s2 r)) = i−I2 (r) ∧ i−I1 j (s1 s2 ) ≤ i−I2 (r) ∧ [i−I1 (s1 ) ∧ i−I1 (s2 )] = [i−I2 (r) ∧ i−I1 (s1 )] ∧ [i−I2 (r) ∧ i−I1 (s2 )] = i−(I1 ⊠I2 ) (s1 r) ∧ i−(I1 ⊠I2 ) (s2 r), i+(I1 j ⊠I2 j ) ((s1 r)(s2 r)) = i+I2 (r) ∧ i+I1 j (s1 s2 ) ≤ i+I2 (r) ∧ [i+I1 (s1 ) ∧ i+I1 (s2 )] = [i+I2 (r) ∧ i+I1 (s1 )] ∧ [i+I2 (r) ∧ i+I1 (s2 )] = i+(I1 ⊠I2 ) (s1 r) ∧ i+(I1 ⊠I2 ) (s2 r),
f(I−1 j ⊠I2 j ) ((s1 r)(s2 r)) = fI−2 (r) ∧ fI−1 j (s1 s2 ) ≤ fI−2 (r) ∧ [ fI−1 (s1 ) ∧ fI−1 (s2 )] = [ fI−2 (r) ∧ fI−1 (s1 )] ∧ [ fI−2 (r) ∧ fI−1 (s2 )] = f(I−1 ⊠I2 ) (s1 r) ∧ f(I−1 ⊠I2 ) (s2 r), f(I+1 j ⊠I2 j ) ((s1 r)(s2 r)) = fI+2 (r) ∧ fI+1 j (s1 s2 ) ≤ fI+2 (r) ∧ [ fI+1 (s1 ) ∧ fI+1 (s2 )] = [ fI+2 (r) ∧ fI+1 (s1 )] ∧ [ fI+2 (r) ∧ fI+1 (s2 )] = f(I+1 ⊠I2 ) (s1 r) ∧ f(I+1 ⊠I2 ) (s2 r), for s1 r, s2 r ∈ U1 ⊠ U2 . Case 3. For r1 r2 ∈ U1 j , s1 s2 ∈ U2 j , t−(I1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = t−I1 j (r1 r2 ) ∧ t−I2 j (s1 s2 ) ≤ [t−I1 (r1 ) ∧ t−I1 (r2 )] ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r1 ) ∧ t−I2 (s1 )] ∧ [t−I1 (r2 ) ∧ t−I2 (s2 )] = t−(I1 ⊠I2 ) (r1 s1 ) ∧ t−(I1 ⊠I2 ) (r2 s2 ), t+(I1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = t+I1 j (r1 r2 ) ∧ t+I2 j (s1 s2 ) ≤ [t+I1 (r1 ) ∧ t+I1 (r2 )] ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r1 ) ∧ t+I2 (s1 )] ∧ [t+I1 (r2 ) ∧ t+I2 (s2 )] = t+(I1 ⊠I2 ) (r1 s1 ) ∧ t+(I1 ⊠I2 ) (r2 s2 ),
70
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
71
i−(I1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = i−I1 j (r1 r2 ) ∧ i−I2 j (s1 s2 ) ≤ [i−I1 (r1 ) ∧ i−I1 (r2 )] ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r1 ) ∧ i−I2 (s1 )] ∧ [i−I1 (r2 ) ∧ i−I2 (s2 )] = i−(I1 ⊠I2 ) (r1 s1 ) ∧ i−(I1 ⊠I2 ) (r2 s2 ), i+(I1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = i+I1 j (r1 r2 ) ∧ i+I2 j (s1 s2 ) ≤ [i+I1 (r1 ) ∧ i+I1 (r2 )] ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r1 ) ∧ i+I2 (s1 )] ∧ [i+I1 (r2 ) ∧ i+I2 (s2 )] = i+(I1 ⊠I2 ) (r1 s1 ) ∧ i+(I1 ⊠I2 ) (r2 s2 ), f(I−1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = fI−1 j (r1 r2 ) ∧ fI−2 j (s1 s2 ) ≤ [ fI−1 (r1 ) ∧ fI−1 (r2 )] ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r1 ) ∧ fI−2 (s1 )] ∧ [ fI−1 (r2 ) ∧ fI−2 (s2 )] = f(IP1 ⊠I2 ) (r1 s1 ) ∧ f(I−1 ⊠I2 ) (r2 s2 ), f(I+1 j ⊠I2 j ) ((r1 s1 )(r2 s2 )) = fI+1 j (r1 r2 ) ∧ fI+2 j (s1 s2 ) ≤ [ fI+1 (r1 ) ∧ fI+1 (r2 )] ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r1 ) ∧ fI+2 (s1 )] ∧ [ fI+1 (r2 ) ∧ fI+2 (s2 )] = f(I+1 ⊠I2 ) (r1 s1 ) ∧ f(I+1 ⊠I2 ) (r2 s2 ), r1 s1 , r2 s2 ∈ U1 ⊠ U2 . All cases hold for all j ∈ {1, 2, . . . , t}. This completes the proof. Definition 3.15. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs. Composition of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 ◦ Gˇ iv2 = (I1 ◦ I2 , I11 ◦ I21 , I12 ◦ I22 , . . . , I1t ◦ I2t ), is defined as: − t(I ◦I ) (rs) = (t−I ◦ t−I )(rs) = t−I (r) ∧ t−I (s) i− 1 2 (rs) = (i−1 ◦ i−2)(rs) = i−1(r) ∧ i− 2(s) (i) I1 I2 I1 I2 (I1 ◦I2 ) f − (rs) = ( f − ◦ f − )(rs) = f − (r) ∧ f − (s) I1 I2 I1 I2 (I1 ◦I2 )
+ t(I ◦I ) (rs) = (t+I ◦ t+I )(rs) = t+I (r) ∧ t+I (s) i+ 1 2 (rs) = (i+1 ◦ i+2)(rs) = i+1(r) ∧ i+ 2(s) (ii) I1 I2 I1 I2 (I1 ◦I2 ) f(I+ ◦I ) (rs) = ( fI+ ◦ fI+ )(rs) = fI+ (r) ∧ fI+ (s) 1 2 1 2 1 2 for all rs ∈ U1 × U2 ,
− t(I1 j ◦I2 j ) (rs1 )(rs2 ) = (t−I1 j ◦ t−I2 j )(rs1 )(rs2 ) = t−I1 (r) ∧ t−I2 j (s1 s2 ) i− (rs1 )(rs2 ) = (i−I1 j ◦ i−I2 j )(rs1 )(rs2 ) = i−I1 (r) ∧ i−I2 j (s1 s2 ) (iii) (I1 j ◦I2 j ) f− (rs1 )(rs2 ) = ( fI−1 j ◦ fI−2 j )(rs1 )(rs2 ) = fI−1 (r) ∧ fI−2 j (s1 s2 ) (I1 j ◦I2 j )
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
+ t(I1 j ◦I2 j ) (rs1 )(rs2 ) = (t+I1 j ◦ t+I2 j )(rs1 )(rs2 ) = t+I1 (r) ∧ t+I2 j (s1 s2 ) i+ (rs1 )(rs2 ) = (i+I1 j ◦ i+I2 j )(rs1 )(rs2 ) = i+I1 (r) ∧ i+I2 j (s1 s2 ) (iv) (I1 j ◦I2 j ) + f (rs1 )(rs2 ) = ( fI+1 j ◦ fI+2 j )(rs1 )(rs2 ) = fI+1 (r) ∧ fI+2 j (s1 s2 ) (I1 j ◦I2 j ) for all r ∈ U1 , s1 s2 ∈ U2 j , − t(I1 j ◦I2 j ) (r1 s)(r2 s) = (t−I1 j ◦ t−I2 j )(r1 s)(r2 s) = t−I2 (s) ∧ t−I1 j (r1 r2 ) i− (r s)(r2 s) = (i−I1 j ◦ i−I2 j )(r1 s)(r2 s) = i−I2 (s) ∧ i−I1 j (r1 r2 ) (v) (I1 j ◦I2 j ) 1 f− (r s)(r2 s) = ( fI−1 j ◦ fI−2 j )(r1 s)(r2 s) = fI−2 (s) ∧ fI−1 j (r1 r2 ) (I1 j ◦I2 j ) 1
+ t(I1 j ◦I2 j ) (r1 s)(r2 s) = (t+I1 j ◦ t+I2 j )(r1 s)(r2 s) = t+I2 (s) ∧ t+I1 j (r1 r2 ) i+ (r s)(r2 s) = (i+I1 j ◦ i+I2 j )(r1 s)(r2 s) = i+I2 (s) ∧ i+I1 j (r1 r2 ) (vi) (I1 j ◦I2 j ) 1 f+ (r s)(r2 s) = ( fI+1 j ◦ fI+2 j )(r1 s)(r2 s) = fI+2 (s) ∧ fI+1 j (r1 r2 ) (I1 j ◦I2 j ) 1 for all s ∈ U2 , r1 r2 ∈ U1 j . − t(I1 j ◦I2 j ) (r1 s1 )(r2 s2 ) = (t−I1 j ◦ t−I2 j )(r1 s1 )(r2 s2 ) = t−I1 j (r1 r2 ) ∧ t−I2 (s1 ) ∧ t−I2 (s2 ) i− (r s )(r2 s2 ) = (i−I1 j ◦ i−I2 j )(r1 s1 )(r2 s2 ) = i−I1 j (r1 r2 ) ∧ i−I2 (s1 ) ∧ i−I2 (s2 ) (vii) (I1 j ◦I2 j ) 1 1 − f (r s )(r2 s2 ) = ( fI−1 j ◦ fI−2 j )(r1 s1 )(r2 s2 ) = fIP1 j (r1 r2 ) ∧ fI−2 (s1 ) ∧ fI−2 (s2 ) (I1 j ◦I2 j ) 1 1
+ t(I1 j ◦I2 j ) (r1 s1 )(r2 s2 ) = (t+I1 j ◦ t+I2 j )(r1 s1 )(r2 s2 ) = t+I1 j (r1 r2 ) ∧ t+I2 (s1 ) ∧ t+I2 (s2 ) i+ (r s )(r2 s2 ) = (i+I1 j ◦ i+I2 j )(r1 s1 )(r2 s2 ) = i+I1 j (r1 r2 ) ∧ i+I2 (s1 ) ∧ i+I2 (s2 ) (viii) (I1 j ◦I2 j ) 1 1 f+ (r s )(r2 s2 ) = ( fI+1 j ◦ fI+2 j )(r1 s1 )(r2 s2 ) = fI+1 j (r1 r2 ) ∧ fI+2 (s1 ) ∧ fI+2 (s2 ) (I1 j ◦I2 j ) 1 1 for all r1 r2 ∈ U1 j , s1 s2 ∈ U2 j such that s1 , s2 . Example 3.16. Composition of IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 ◦ Gˇ iv2 = {I1 ◦ I2 , I11 ◦ I21 , I12 ◦ I22 } and is depicted in Fig. 11 and Fig. 12. r2 s3 ([0.5, 0.6], [0.3, 0.4], [0.5, 0.6])
r1 s2 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
1
◦
I2
1(
[0 .2 ,0 .3 ] I11 ◦ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) , [0. 2, 0. 3] ,[ r2 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) 0. 3, 0. 4] ) I11 ◦ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
I1
I1
1
◦
I2
2
◦
2(
[0 .3 ,0 .4 [0 ], .3 [0 ,0 .2 .4 ,0 ], .3 [0 ], .2 [0 ,0 .4 .3 ,0 ], .5 [0 ]) .4 ,0 .5 ])
1(
b
r2 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I2
I11 ◦ I21 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6])
I1
I11 ◦ I21 ([0.3, 0.4], [0.2, 0.3], [0.4, 0.5])
b
I 11
.2, ([0 21 I ◦
b
I11 ◦ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
.2, , [0 ] 3 0.
I11 ◦ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
]) 0.5 ) .4, 0 5] 0. ], [ 4, 0.3 0. , [ .2 ], .4 , [0 ,0 .4] .3 0 0 ,[ .3, 4] ([0 0. 21 3, I . ◦ ([0 I 11 22 ◦I 2 I1
b
r1 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
]) 0.4 .3, 0 ], [ 0.3
b
I11 ◦ I21 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r1 s3 ([0.5, 0.6], [0.2, 0.3], [0.5, 0.6])
Figure 11: Gˇ iv1 ◦ Gˇ iv2
72
b
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80 r3 s3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
r3 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I1
1
◦I
◦
I2
2
1(
[0 .2 ,0 .3 ] I12 ◦ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) , [0. 2, 0. 3] ,[ r3 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4]) 0. 3, 0. 4] ) I12 ◦ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
I1
I1
2
◦
I2
2
◦
2(
[0 .3 ,0 .4 [0 ], .3 [0 ,0 .3 .4 ,0 ], .4 [0 ], .3 [0 ,0 .4 .4 ,0 ], .5 [0 ]) .4 ,0 .5 ])
2(
b
b
r4 s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
I2
I12 ◦ I22 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
I 11
I12 ◦ I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
b
b
I12 ◦ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
.2, , [0 .3] 0 .2, ([0 1
I12 ◦ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
) .5] ,0 4 . ]) .5 , [0 ,0 .4] .4 0 0 [ .3, ], .4 , [0 ,0 .4] .3 0 0 ,[ .3, 4] ([0 0. 22 3, I . ◦ ([0 I 12 22 ◦I 2 I1
b
r4 s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
) .4] ,0 3 . 0 ], [ 0.3
b
I12 ◦ I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r4 s3 ([0.4, 0.5], [0.3, 0.4], [0.5, 0.6])
Figure 12: Gˇ iv1 ◦ Gˇ iv2
Theorem 3.17. Composition Gˇ iv1 ◦ Gˇ iv2 = (I1 ◦ I2 , I11 ◦ I21 , I12 ◦ I22 , . . . , I1t ◦ I2t ) of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively is an IVNGS of Gs1 ◦ Gs2 . Proof. Consider three cases: Case 1. For r ∈ U1 , s1 s2 ∈ U2 j t−(I1 j ◦I2 j ) ((rs1 )(rs2 )) = t−I1 (r) ∧ t−I2 j (s1 s2 ) ≤ t−I1 (r) ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r) ∧ t−I2 (s1 )] ∧ [t−I1 (r) ∧ t−I2 (s2 )] = t−(I1 ◦I2 ) (rs1 ) ∧ t−(I1 ◦I2 ) (rs2 ), t+(I1 j ◦I2 j ) ((rs1 )(rs2 )) = t+I1 (r) ∧ t+I2 j (s1 s2 ) ≤ t+I1 (r) ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r) ∧ t+I2 (s1 )] ∧ [t+I1 (r) ∧ t+I2 (s2 )] = t+(I1 ◦I2 ) (rs1 ) ∧ t+(I1 ◦I2 ) (rs2 ),
i−(I1 j ◦I2 j ) ((rs1 )(rs2 )) = i−I1 (r) ∧ i−I2 j (s1 s2 ) ≤ i−I1 (r) ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r) ∧ i−I2 (s1 )] ∧ [i−I1 (r) ∧ i−I2 (s2 )] = i−(I1 ◦I2 ) (rs1 ) ∧ i−(I1 ◦I2 ) (rs2 ),
73
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
i+(I1 j ◦I2 j ) ((rs1 )(rs2 )) = i+I1 (r) ∧ i+I2 j (s1 s2 ) ≤ i+I1 (r) ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r) ∧ i+I2 (s1 )] ∧ [i+I1 (r) ∧ i+I2 (s2 )] = i+(I1 ◦I2 ) (rs1 ) ∧ i+(I1 ◦I2 ) (rs2 ),
f(I−1 j ◦I2 j ) ((rs1 )(rs2 )) = fI−1 (r) ∧ fI−2 j (s1 s2 ) ≤ fI−1 (r) ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r) ∧ fI−2 (s1 )] ∧ [ fI−1 (r) ∧ fI−2 (s2 )] = f(I−1 ◦I2 ) (rs1 ) ∧ f(I−1 ◦I2 ) (rs2 ), f(I+1 j ◦B2 j ) ((rs1 )(rs2 )) = fI+1 (r) ∧ fI+2 j (s1 s2 ) ≤ fI+1 (r) ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r) ∧ fI+2 (s1 )] ∧ [ fI+1 (r) ∧ fI+2 (s2 )] = f(I+1 ◦I2 ) (rs1 ) ∧ f(I+1 ◦I2 ) (rs2 ), rs1 , rs2 ∈ U1 ◦ U2 . Case 2. For r ∈ U2 , s1 s2 ∈ U1 j t−(I1 j ◦I2 j ) ((s1 r)(s2 r)) = t−I2 (r) ∧ t−I1 j (s1 s2 ) ≤ t−I2 (r) ∧ [t−I1 (s1 ) ∧ t−I1 (s2 )] = [t−I2 (r) ∧ t−I1 (s1 )] ∧ [t−I2 (r) ∧ t−I1 (s2 )] = t−(I1 ◦I2 ) (s1 r) ∧ t−(I1 ◦I2 ) (s2 r), t+(I1 j ◦I2 j ) ((s1 r)(s2 r)) = t+I2 (r) ∧ t+I1 j (s1 s2 ) ≤ t+I2 (r) ∧ [t+I1 (s1 ) ∧ t+I1 (s2 )] = [t+I2 (r) ∧ t+I1 (s1 )] ∧ [t+I2 (r) ∧ t+I1 (s2 )] = t+(I1 ◦I2 ) (s1 r) ∧ t+(I1 ◦I2 ) (s2 r), i−(I1 j ◦I2 j ) ((s1 r)(s2 r)) = i−I2 (r) ∧ i−I1 j (s1 s2 ) ≤ i−I2 (r) ∧ [i−I1 (s1 ) ∧ i−I1 (s2 )] = [i−I2 (r) ∧ i−I1 (s1 )] ∧ [i−I2 (r) ∧ i−I1 (s2 )] = i−(I1 ◦I2 ) (s1 r) ∧ i−(I1 ◦I2 ) (s2 r), i+(I1 j ◦I2 j ) ((s1 r)(s2 r)) = i+I2 (r) ∧ i+I1 j (s1 s2 ) ≤ i+I2 (r) ∧ [i+I1 (s1 ) ∧ i+I1 (s2 )] = [i+I2 (r) ∧ i+I1 (s1 )] ∧ [i+I2 (r) ∧ i+I1 (s2 )] = i+(I1 ◦I2 ) (s1 r) ∧ i+(I1 ◦I2 ) (s2 r),
74
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
f(I−1 j ◦I2 j ) ((s1 r)(s2 r)) = fI−2 (r) ∧ fI−1 j (s1 s2 ) ≤ fI−2 (r) ∧ [ fI−1 (s1 ) ∧ fI−1 (s2 )] = [ fI−2 (r) ∧ fI−1 (s1 )] ∧ [ fI−2 (r) ∧ fI−1 (s2 )] = f(I−1 ◦I2 ) (s1 r) ∧ f(I−1 ◦I2 ) (s2 r), f(I+1 j ◦I2 j ) ((s1 r)(s2 r)) = fI+2 (r) ∧ fI+1 j (s1 s2 ) ≤ fI+2 (r) ∧ [ fI+1 (s1 ) ∧ fI+1 (s2 )] = [ fI+2 (r) ∧ fI+1 (s1 )] ∧ [ fI+2 (r) ∧ fI+1 (s2 )] = f(I+1 ◦I2 ) (s1 r) ∧ f(I+1 ◦I2 ) (s2 r), s1 r, s2 r ∈ U1 ◦ U2 . Case 3. For r1 r2 ∈ U1 j , s1 s2 ∈ U2 j such that s1 , s2 t−(I1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = t−I1 j (r1 r2 ) ∧ t−I2 (s1 ) ∧ t−I2 (s2 ) ≤ [t−I1 (r1 ) ∧ t−I1 (r2 )] ∧ [t−I2 (s1 ) ∧ t−I2 (s2 )] = [t−I1 (r1 ) ∧ t−I2 (s1 )] ∧ [t−I1 (r2 ) ∧ t−I2 (s2 )] = t−(I1 ◦I2 ) (r1 s1 ) ∧ t−(I1 ◦I2 ) (r2 s2 ), t+(I1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = t+I1 j (r1 r2 ) ∧ t+I2 (s1 ) ∧ t+I2 (s2 ) ≤ [t+I1 (r1 ) ∧ t+I1 (r2 )] ∧ [t+I2 (s1 ) ∧ t+I2 (s2 )] = [t+I1 (r1 ) ∧ t+I2 (s1 )] ∧ [t+I1 (r2 ) ∧ t+I2 (s2 )] = t+(I1 ◦I2 ) (r1 s1 ) ∧ t+(I1 ◦I2 ) (r2 s2 ), i−(I1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = i−I1 j (r1 r2 ) ∧ i−I2 (s1 ) ∧ i−I2 (s2 ) ≤ [i−I1 (r1 ) ∧ i−I1 (r2 )] ∧ [i−I2 (s1 ) ∧ i−I2 (s2 )] = [i−I1 (r1 ) ∧ i−I2 (s1 )] ∧ [i−I1 (r2 ) ∧ i−I2 (s2 )] = i−(I1 ◦I2 ) (r1 s1 ) ∧ i−(I1 ◦I2 ) (r2 s2 ), i+(I1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = i+I1 j (r1 r2 ) ∧ i+I2 (s1 ) ∧ i+I2 (s2 ) ≤ [i+I1 (r1 ) ∧ i+I1 (r2 )] ∧ [i+I2 (s1 ) ∧ i+I2 (s2 )] = [i+I1 (r1 ) ∧ i+I2 (s1 )] ∧ [i+I1 (r2 ) ∧ i+I2 (s2 )] = i+(I1 ◦I2 ) (r1 s1 ) ∧ i+(I1 ◦I2 ) (r2 s2 ), f(I−1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = fI−1 j (r1 r2 ) ∧ fI−2 (s1 ) ∧ fI−2 (s2 ) ≤ [ fI−1 (r1 ) ∧ fI−1 (r2 )] ∧ [ fI−2 (s1 ) ∧ fI−2 (s2 )] = [ fI−1 (r1 ) ∧ fI−2 (s1 )] ∧ [ fI−1 (r2 ) ∧ fI−2 (s2 )] = f(I−1 ◦I2 ) (r1 s1 ) ∧ f(I−1 ◦I2 ) (r2 s2 ),
75
76
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
f(I+1 j ◦I2 j ) ((r1 s1 )(r2 s2 )) = fI+1 j (r1 r2 ) ∧ fI+2 (s1 ) ∧ fI+2 (s2 ) ≤ [ fI+1 (r1 ) ∧ fI+1 (r2 )] ∧ [ fI+2 (s1 ) ∧ fI+2 (s2 )] = [ fI+1 (r1 ) ∧ fI+2 (s1 )] ∧ [ fI+1 (r2 ) ∧ fI+2 (s2 )] = f(I+1 ◦I2 ) (r1 s1 ) ∧ f(I+1 ◦I2 ) (r2 s2 ), r1 s1 , r2 s2 ∈ U1 ◦ U2 . All cases hold for all j ∈ {1, 2, . . . , t}. This completes the proof. Definition 3.18. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs. Union of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 ∪ Gˇ iv2 = (I1 ∪ I2 , I11 ∪ I21 , I12 ∪ I22 , . . . , I1t ∪ I2t ), is defined as: − t (r) = (t−I1 ∪ t−I2 )(r) = t−I1 (r) ∨ t−I2 (r) −(I1 ∪I2 ) i(I1 ∪I2 ) (r) = (i−I1 ∪ i−I2 )(r) = i−I1 (r) ∨ i−I2 (r) (i) f(I− ∪I ) (r) = ( fI− ∪ fI− )(r) = fI− (r) ∧ fI− (r) 1 2 1 2 1 2
+ t(I ∪I ) (r) = (t+I ∪ t+I )(r) = t+I (r) ∨ t+I (r) i+ 1 2 (r) = (i+1 ∪ i+2)(r) = i+1(r) ∨ i+ 2(r) (ii) I1 I2 I1 I2 (I1 ∪I2 ) f(I+ ∪I ) (r) = ( fI+ ∪ fI+ )(r) = fI+ (r) ∧ fI+ (r) 1 2 1 2 1 2 for all r ∈ U1 ∪ U2 , − t (rs) = (t−I1 j ∪ t−I2 j )(rs) = t−I1 j (rs) ∨ t−I2 j (rs) −(I1 j ∪I2 j ) i(I1 j ∪I2 j ) (rs) = (i−I1 j ∪ i−I2 j )(rs) = i−I1 j (rs) ∨ i−I2 j (rs) (iii) f− (rs) = ( fI−1 j ∪ fI−2 j )(rs) = fI−1 j (rs) ∧ fI−2 j (rs) (I1 j ∪I2 j )
+ t(I1 j ∪I2 j ) (rs) = (t+I1 j ∪ t+I2 j )(rs) = t+I1 j (rs) ∨ t+I2 j (rs) i+ (rs) = (i+I1 j ∪ i+I2 j )(rs) = i+I1 j (rs) ∨ i+I2 j (rs) (iv) (I1 j ∪I2 j ) + f (rs) = ( fI+1 j ∪ fI+2 j )(rs) = fI+1 j (rs) ∧ fI+2 j (rs) (I1 j ∪I2 j ) for all rs ∈ U1 j ∪ U2 j .
Example 3.19. Union of two IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 ∪ Gˇ iv2 = {I1 ∪ I2 , I11 ∪ I21 , I12 ∪ I22 } and is depicted in Fig. 13. s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
s3 ([0.5, 0.6], [0.4, 0.5], [0.5, 0.6]) I1
2
∪
I2
2 ([
0.3 ,
r2 ([0.5, 0.6], [0.3, 0.4], [0.8, 0.9]) 0.4 b ], [ 0.3 ,
, 0.2 ], [ 0.6 b , .5 ([0
I 11
∪
b b
0.4 ], [ 0.4 ,
r4 ([0.4, 0.5], [0.3, 0.4], [0.6, 0.7])
0.5 ])
I 11
I1
]) 0.7 6, . 0 ], [ 0.3
I 21
b
s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
2
∪
∪
.2, ([0 I 21
I2
, 0.3 ], [ b 0.3 , 0.2 ], [ 0.3
]) 0.4
2 ([
0.4 ,
0.5 ], [ 0.3 , b
0.4 ], [ 0.4 ,
0.5 ])
r3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
r1 ([0.5, 0.6], [0.2, 0.3], [0.6, 0.7])
Figure 13: Gˇ iv1 ∪ Gˇ iv2
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
77
Theorem 3.20. Union Gˇ iv1 ∪ Gˇ iv2 = (I1 ∪ I2 , I11 ∪ I21 , I12 ∪ I22 , . . . , I1t ∪ I2t ) of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 is an IVNGS of Gs1 ∪ Gs2 . Theorem 3.21. If Gs = (U1 ∪ U2 , U11 ∪ U21 , U12 ∪ U22 , . . . , U1t ∪ U2t ) is union of two graph structures Gs1 = (U1 , U11 , U12 , . . . , U1t ) and Gs2 = (U2 , U21 , U22 , . . . , U2t ), then every IVNGS Gˇ iv = (I, I1 , I2 , . . . , It ) of Gs is union of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively. Proof. Firstly, we define I1 , I2 , I1 j and I2 j for j ∈ {1, 2, . . . , t} as: t−I1 (r) = t−I (r), i−I1 (r) = i−I (r), fI−1 (r) = fI− (r), t+I1 (r) = t+I (r), i+I1 (r) = i+I (r), fI+1 (r) = fI+ (r), if r ∈ U1 . t−I2 (r) = t−I (r), i−I2 (r) = i−I (r), fI−2 (r) = fI− (r), t+I2 (r) = t+I (r), i+I2 (r) = i+I (r), fI+2 (r) = fI+ (r), if r ∈ U2 . t−I1 j (r1 r2 ) = t−I j (r1 r2 ), t+I1 j (r1 r2 ) = t+I j (r1 r2 ), t−I2 j (r1 r2 ) = t−I j (r1 r2 ), t+I2 j (r1 r2 ) = t+I j (r1 r2 ),
i−I1 j (r1 r2 ) = i−I j (r1 r2 ), i+I1 j (r1 r2 ) = i+I j (r1 r2 ), i−I2 j (r1 r2 ) = i−I j (r1 r2 ), i+I2 j (r1 r2 ) = i+I j (r1 r2 ),
fI−1 j (r1 r2 ) = fI+1 j (r1 r2 ) = fI−2 j (r1 r2 ) = fI+2 j (r1 r2 ) =
fI−j (r1 r2 ), fI+j (r1 r2 ), if r1 r2 ∈ U1 j . fI−j (r1 r2 ), fI+j (r1 r2 ), if r1 r2 ∈ U2 j .
Then I = I1 ∪ I2 and I j = I1 j ∪ I2 j , j ∈ {1, 2, . . . , t}. Now for r1 r2 ∈ Uk j , t−Ikj (r1 r2 ) = t−I j (r1 r2 ) ≤ t−I (r1 ) ∧ t−I (r2 ) = t−Ik (r1 ) ∧ t−Ik (r2 ), i−Ikj (r1 r2 ) = i−I j (r1 r2 ) ≤ i−I (r1 ) ∧ i−I (r2 ) = i−Ik (r1 ) ∧ i−Ik (r2 ), fI−kj (r1 r2 ) = fI−j (r1 r2 ) ≤ fI− (r1 ) ∧ fI− (r2 ) = fI−k (r1 ) ∧ fI−k (r2 ), t+Ikj (r1 r2 ) = t+I j (r1 r2 ) ≤ t+I (r1 ) ∧ t+I (r2 ) = t+Ik (r1 ) ∧ t+Ik (r2 ), i+Ikj (r1 r2 ) = i+I j (r1 r2 ) ≤ i+I (r1 ) ∧ i+I (r2 ) = i+Ik (r1 ) ∧ i+Ik (r2 ), fI+kj (r1 r2 ) = fI+j (r1 r2 ) ≤ fI+ (r1 ) ∧ fI+ (r2 ) = fI+k (r1 ) ∧ fI+k (r2 ), Hence Gˇ ivk = (Ik , Ik1 , Ik2 , . . . , Ikt ) is an IVNGS of graph structure Gsk , k = 1, 2. Thus Gˇ iv = (I, I1 , I2 , . . . , It ) an IVNGS of Gs = Gs1 ∪ Gs2 , is union of two IVNGSs Gˇ iv1 and Gˇ iv2 . Definition 3.22. Let Gˇ iv1 = (I1 , I11 , I12 , . . . , I1t ) and Gˇ iv2 = (I2 , I21 , I22 , . . . , I2t ) be two IVNGSs and U1 ∩ U2 = ∅. Join of Gˇ iv1 and Gˇ iv2 , denoted by Gˇ iv1 + Gˇ iv2 = (I1 + I2 , I11 + I21 , I12 + I22 , . . . , I1t + I2t ), is defined as: − t (r) = t−(I1 ∪I2 ) (r) −(I1 +I2 ) i(I1 +I2 ) (r) = i−(I1 ∪I2 ) (r) (i) f(I− +I ) (r) = f(I− ∪I ) (r) 1 2 1 2
+ t(I +I ) (r) = t+(I ∪I ) (r) i+ 1 2 (r) = i+ 1 2 (r) (ii) (I1 +I2 ) (I1 ∪I2 ) f(I+ +I ) (r) = f(I+ ∪I ) (r) 1 2 1 2 for all r ∈ U1 ∪ U2 , − t (rs) = t−(I1 j ∪I2 j ) (rs) −(I1 j +I2 j ) i(I1 j +I2 j ) (rs) = i−(I1 j ∪I2 j ) (rs) (iii) f− (rs) = f(I−1 j ∪I2 j ) (rs) (I1 j +I2 j )
78
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
+ t(I1 j +I2 j ) (rs) = t+(I1 j ∪I2 j ) (rs) i+ (rs) = i+(I1 j ∪I2 j ) (rs) (iv) (I1 j +I2 j ) + f (rs) = f(I+1 j ∪I2 j ) (rs) (I1 j +I2 j ) for all rs ∈ U1 j ∪ U2 j , − t (rs) = (t−I1 j + t−I2 j )(rs) = t−I1 (r) ∧ t−I2 (s) −(I1 j +I2 j ) i(I1 j +I2 j ) (rs) = (i−I1 j + i−I2 j )(rs) = i−I1 (r) ∧ i−I2 (s) (v) f− (rs) = ( fI−1 j + fI−2 j )(rs) = fI−1 (r) ∧ fI−2 (s) (I1 j +I2 j )
+ t(I1 j +I2 j ) (rs) = (t+I1 j + t+I2 j )(rs) = t+I1 (r) ∧ t+I2 (s) i+ (rs) = (i+I1 j + i+I2 j )(rs) = i+I1 (r) ∧ i+I2 (s) (vi) (I1 j +I2 j ) + f (rs) = ( fI+1 j + fI+2 j )(rs) = fI+1 (r) ∧ fI+2 (s) (I1 j +I2 j ) for all r ∈ U1 , s ∈ U2 .
Example 3.23. Join of two IVNGSs Gˇ iv1 and Gˇ iv2 shown in Fig. 2 is defined as Gˇ iv1 + Gˇ iv2 = {I1 + I2 , I11 + I21 , I12 + I22 } and is depicted in Fig. 14. ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
b
I12 + I22 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
b
s2 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5]) ]) ([0.3 0.5 ,0 4, .4] . 0 0.4 , [0 ], [ ], [ 4 .3, . 0 0.5 , 0.4 3 . ,0 0 [ ], [ , .6] ] 0.4 4 . ) b 0 , ,0 3 . .5] ([0 ) r2 ([0.5, 0.6], [0.3, 0.4], [0.8, 0.9])
b
I11 + I21 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
I12 + I22 ([0.3, 0.4], [0.3, 0.4], [0.4, 0.5])
.5, ([0b ([0 .5, 0.6 ], [ 0.3 ,
.3, ([0
]) 0.5 .4, 0 [ , .4] ,0 0.3 [ , ] 0.4
([0 .2,
0.3 ], [ 0.2 ,
0.3 ], [ 0.3 ,
b
, 0.2 ], [ 0.3 , 2 . ([0
0. ], [ 0.3
Figure 14: Gˇ iv1 + Gˇ iv2
Theorem 3.24. Join Gˇ iv1 + Gˇ iv2 = (I1 + I2 , I11 + I21 , I12 + I22 , . . . , I1t + I2t ) of two IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively is IVNGS of Gs1 + Gs2 . Theorem 3.25. If Gs = (U1 + U2 , U11 + U21 , U12 + U22 , . . . , U1t + U2t ) is join of two GSs Gs1 = (U1 , U11 , U12 , . . . , U1t ) and Gs2 = (U2 , U21 , U22 , . . . , U2t ), then every strong IVNGS Gˇ iv = (I, I1, I2 , . . . , It ) of Gs is join of two strong IVNGSs Gˇ iv1 and Gˇ iv2 of graph structures Gs1 and Gs2 , respectively.
t−Ikj (r1 r2 ) = t−I j (r1 r2 ), i−Ikj (r1 r2 ) = i−Ikj (r1 r2 ), fI−kj (r1 r2 ) = fI−j (r1 r2 ), t+Ikj (r1 r2 ) = t+I j (r1 r2 ), i+Ikj (r1 r2 ) = i+Ikj (r1 r2 ), fI+kj (r1 r2 ) = fI+j (r1 r2 ), if r1 r2 ∈ Uk j . Now for r1 r2 ∈ Uk j , k = 1, 2, j = 1, 2, . . . , t t−Ikj (r1 r2 ) = t−I j (r1 r2 ) = t−I (r1 ) ∧ t−I (r2 ) = t−Ik (r1 ) ∧ t−Ik (r2 ),
) .4] 3, 0
r3 ([0.4, 0.5], [0.3, 0.4], [0.4, 0.5])
([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
Proof. We define Ik and Ik j for k = 1, 2 and j = 1, 2, . . . , t as: t−Ik (r) = t−I (r), i−Ik (r) = i−I (r), fI−k (r) = fI− (r), t+Ik (r) = t+I (r), i+Ik (r) = i+I (r), fI+k (r) = fI+ (r), if r ∈ Uk
0.4 ])
s1 ([0.2, 0.3], [0.2, 0.3], [0.3, 0.4])
r4 ([0.4, 0.5], [0.3, 0.4], [0.6, 0.7])
r1 ([0.5, 0.6], [0.2, 0.3], [0.6, 0.7]) ([0 b .3, 0.4 ]) 6 . ], [ 0 , 0.2 5 . 0 , 0. [ , 3], ] .3 [0. 0 , 4, 0 2 . 0 .5] [ , ] ) 6 0. I11 + I21 ([0.5, 0.6], [0.2, 0.3], [0.6, 0.7])
s3 ([0.5, 0.6], [0.4, 0.5], [0.5, 0.6])
([0.4, 0.5], [0.3, 0.4], [0.5, 0.6])
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80
79
i−Ikj (r1 r2 ) = i−I j (r1 r2 ) = i−I (r1 ) ∧ i−I (r2 ) = i−Ik (r1 ) ∧ i−Ik (r2 ), fI−kj (r1 r2 ) = fI−j (r1 r2 ) = fI− (r1 ) ∧ fI− (r2 ) = fI−k (r1 ) ∧ fI−k (r2 ), t+Ikj (r1 r2 ) = t+I j (r1 r2 ) = t+I (r1 ) ∧ t+I (r2 ) = t+Ik (r1 ) ∧ t+Ik (r2 ), i+Ikj (r1 r2 ) = i+I j (r1 r2 ) = i+I (r1 ) ∧ i+I (r2 ) = i+Ik (r1 ) ∧ i+Ik (r2 ), fI+kj (r1 r2 ) = fI+j (r1 r2 ) = fI+ (r1 ) ∧ fI+ (r2 ) = fI+k (r1 ) ∧ fI+k (r2 ), Hence Gˇ ivk = (Ik , Ik1 , Ik2 , . . . , Ikt ) is a strong IVNGS of graph structure Gsk , k = 1, 2. Moreover, we will show that Gˇ iv is join of Gˇ iv1 and Gˇ iv2 . According to the definitions 3.18 and 3.22, I = I1 ∪ I2 = I1 + I2 and I j = I1 j ∪ I2 j = I1 j + I2 j , for all r1 r2 ∈ U1 j ∪ U2 j . When r1 r2 ∈ U1 j + U2 j (U1 j ∪ U2 j ), that is, r1 ∈ U1 and r2 ∈ U2 , t−I j (r1 r2 ) = t−I (r1 ) ∧ t−I (r2 ) = t−Ik (r1 ) ∧ t−Ik (r2 ) = t−(I1 j +I2 j ) (r1 r2 ), i−I j (r1 r2 ) = i−I (r1 ) ∧ i−I (r2 ) = i−Ik (r1 ) ∧ i−Ik (r2 ) = i−(I1 j +I2 j ) (r1 r2 ), fI−j (r1 r2 ) = fI− (r1 ) ∧ fI− (r2 ) = fI−k (r1 ) ∧ fI−k (r2 ) = f(I−1 j +I2 j ) (r1 r2 ), t+I j (r1 r2 ) = t+I (r1 ) ∧ t+I (r2 ) = t+Ik (r1 ) ∧ t+Ik (r2 ) = t+(I1 j +I2 j ) (r1 r2 ), i+I j (r1 r2 ) = i+I (r1 ) ∧ i+I (r2 ) = i+Ik (r1 ) ∧ i+Ik (r2 ) = i+(I1 j +I2 j ) (r1 r2 ), fI+j (r1 r2 ) = fI+ (r1 ) ∧ fI+ (r2 ) = fI+k (r1 ) ∧ fI+k (r2 ) = f(I+1 j +I2 j ) (r1 r2 ). When r1 ∈ U2 , r2 ∈ U1 , we get similar calculations. It’s true for j = 1, 2, . . . , t. This completes the proof. We have defined the concept of interval-valued neutrosophic line graphs in Definition 2.3. Thus, we close this research article with the following open problems: Problem 1. Prove or disprove that interval-valued neutrosophic line graph structures are generalization of interval-valued neutrosophic line graphs. Problem 2. Prove or disprove that if f is a weak isomorphism of interval-valued neutrosophic graph structures onto interval-valued neutrosophic line graph structures, then f is an isomorphism. Acknowledgement. The authors are grateful to the reviewer’s valuable comments that improved the quality of our paper. References [1] M. Akram, Interval-valued fuzzy line graphs, Neural Computing & Applications, 21(2012) 145-150. [2] M. Akram and W.A. Dudek, Interval-valued fuzzy graphs, Computers Math. Appl., 61(2011) 289-299. [3] M. Akram, N.O. Al-Shehrie and W.A. Dudek, Certain types of interval-valued fuzzy graphs, Journal of Applied Mathematics, Volume 2013 Article ID 857070(2013) 11 pages. [4] M. Akram, W.A. Dudek and M. Murtaza Yousaf, Self centered interval-valued fuzzy graphs, Afrika Matematika, 26(5-6)(2015) 887-898. [5] M. Akram and M. Nasir, Concepts of interval-valued neutrosophic graphs, International Journal of Algebra and Statistics, 6(1-2)(2017) 22-41 DOI :10.20454/ijas.2017.1235. [6] M. Akram and S. Shahzadi, Neutrosophic soft graphs with application, Journal of Intelligent & Fuzzy Systems, 32(1)(2017) 841-858. [7] M. Akram, Single-valued neutrosophic planar graphs, International Journal of Algebra and Statistics, 5(2)(2016) 157-167. [8] M. Akram and G. Shahzadi, Operations on single-valued neutrosophic graphs, Journal of Uncertain System, 11(2)(2017) 1-26. [9] M. Akram and R. Akmal, Application of bipolar fuzzy sets in graph structures, Applied Computational Intelligence and Soft Computing, 2016(2016), Article ID 5859080, 13 pages. [10] K. Atanassov, Intuitionistic fuzzy sets, Fuzzy sets and Systems, 20(1986) 87-96. [11] P. Bhattacharya, Some remarks on fuzzy graphs, Pattern Recognition Letter, 6(1987) 297-302. [12] T. Dinesh, A study on graph structures, incidence algebras and their fuzzy analogues[Ph.D.thesis], Kannur University, Kannur, India, (2011). [13] T. Dinesh and T.V. Ramakrishnan, On generalised fuzzy graph structures, Applied Mathematical Sciences, 5(4)(2011) 173 − 180. [14] J. Hongmei and W. Lianhua, Interval-valued fuzzy subsemigroups and subgroups sssociated by intervalvalued suzzy graphs, 2009 WRI Global Congress on Intelligent Systems, (2009) 484-487.
M. Akram and M. Sitara / Int. J. of Algebra and Statistics 6 (2017), 56-80 [15] [16] [17] [18] [19] [20] [21] [22] [23] [24] [25] [26] [27] [28]
80
A. Kaufmann, Introduction a la Thiorie des Sous-Ensemble Flous, Masson et Cie, 1(1973). J.N. Mordeson, C.S. Peng, Operations on fuzzy graphs, Information Sci. 79 (1994) 159-170. A. Rosenfeld, Fuzzy graphs, Fuzzy Sets and Their Applications, Academic Press, New York, (1975) 77-95. E. Sampathkumar, Generalized graph structures, Bulletin of Kerala Mathematics Association, 3(2)(2006) 65 â&#x2C6;&#x2019; 123. F. Smarandache, A unifying field in logics. neutrosophy: neutrosophic probability, set and logic. Rehoboth:, American Research Press, (1999). F. Smarandache, Neutrosophic set- a generalization of the intuitionistic fuzzy set, Granular Computing. 2006 IEEE International Conference, (2006) 38-42 DOI: 10.1109/GRC.2006.1635754. M.S. Sunitha, A. Vijayakumar, Complement of a fuzzy graph, Indian J. Pure Appl. Math. 33(2002) 1451-1464. H. Wang, F. Smarandache, Y.Q. Zhang and R. Sunderraman, Single-valued neutrosophic sets, Multisspace and Multistruct, 4(2010) 410-413. H. Wang, Y. Zhang and R. Sunderraman, Truth-value based interval neutrosophic sets, Granular Computing, 2005 IEEE International Conference, 1(2005) 274-277 DOI: 10.1109/GRC.2005.1547284. H. Wang, F. Smarandache, Y.Q. Zhang and R. Sunderram, An Interval neutrosophic sets and logic: theory and applications in computing, Hexis Arizona, (2005). J. Ye, Similarity measures between interval neutrosophic sets and their applications in multicriteria decision-making, Journal of Intelligent & Fuzzy Systems, 26(2014) 165-172. L.A. Zadeh, Fuzzy sets, Information Control, 8(1965) 338-353. L.A. Zadeh, The concept of a linguistic variable and its application to approximate reasoning I, Information Sci., 8(1975) 199-249. L.A. Zadeh, Similarity relations and fuzzy orderings, Information Sciences, 3(2)(1971) 177 â&#x2C6;&#x2019; 200.
The author has requested enhancement of the downloaded file. All in-text references underlined in blue are linked to publications on ResearchGate.